Participation/collaboration pattern: Perspectives of trust and security risks - Hina, S. (Institute of Electrical and Electronics Engineers Inc., 2014)
Cyber security issues, due to a lack of trust in social networking sites (SNS), are being addressed by many researchers and practitioners. Despite the diversity of security and privacy vulnerabilities, SNS have acquired and are still acquiring great popularity. Cybercrimes exploiting flaws in information technology and the imprudent trust of users, in who they add as contacts, are alarming and can lead to serious consequences in terms of identity theft, harassment, cyber bullying and defamation. People share personal and sensitive information on profiles and trust SNS service providers and friends to keep their information private. Our study reveals that trust in SNS and trust in friends are two different perspectives of the factor 'trust' which can be predicted by 'security', 'privacy' and 'cyber safety education' factors. Moreover, trust is a vital factor that affects the intention of a user to participate in the collaborative sharing pattern. A multiple regression analysis has been used to validate the proposed research framework. The results from 380 SNS users in a school community, including students, teachers, parents and school admin show that perceived privacy and security in SNS are the antecedents of trust in SNS while cyber safety education is the antecedent of trust in friends. Sensible levels of trust aid people in collaborating safely using SNS. 'Trust' also influences the intention to use SNS for participation/collaboration among users. Â© 2014 IEEE.